Religiosity, Spirituality, and Health Among African American Adolescents and Emerging Adults Living in the USA: A Scoping Review of the Literature - Harrell, Crystal T. (Journal of religion and health, 2025)
The relationship between religion and/or spirituality (R/S) and health among adolescents and emerging adults has been extensively examined in the last decade. However, very few studies have explored this association among African American youth. Many studies predominantly use religious metrics to assess this relationship. However, growing evidence highlights the need to diversify measures when examining faith's role in African Americans’ lives. This scoping review examines the understudied relationship between R/S and health among African American adolescents and emerging adults (ages 12-19). The review synthesized data from seven articles out of 154 identified, revealing a positive association between R/S and health outcomes among this population. The study underscores the need for deeper exploration and the potential for faith-based interventions tailored to African American adolescents and emerging adults.